Spark Plasma Sintering and tribological behavior of Ti3SiC2–Ti5Si3–TiC composites. Issue 17 (1st December 2019) - Benamor, A.; Hadji, Y.; Chiker, N.; Haddad, A.; Guedouar, B.; Labaiz, M.; Hakem, M.; Tricoteaux, A.; Nivot, C.; Erauw, J.P.; Badji, R.; Hadji, M.
Abstract: Herein, we study the effect of TiC content on the tribological behavior of four Ti3 SiC2 /Ti5 Si3 /TiC composites, prepared through Spark Plasma Sintering. The tribological properties were investigated under dry sliding, against Al2 O3 counterpart at room temperature, under different normal loads and sliding speeds. Vickers indentation results showed that the composites preserve some damage tolerance properties. Scanning Electron Microscopy (SEM) and Raman spectroscopy results showed that the low wear stage is associated with the formation of a lubricious tribofilm consisting of a mixture of Ti6 O11 Magnéli-phase and graphitic carbon. On the other hand, the tribo-oxidation products of the free TiC composite were identified as a mixture of TiO2 and SiO2 oxides. The composite reinforced up to 25 wt % TiC showed no transition from the low to the high wear rate as a function of normal loads. The influence of processing variables on microstructure development and wear mechanisms of the composites is discussed.